2021
DOI: 10.3390/cells10113234
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Factorial Observational Study on Sequential Fecal Microbiota Transplant in Patients with Medically Refractory Clostridioides difficile Infection

Abstract: Fecal microbiota transplantation (FMT) is highly effective in recurrent Clostridioides difficile infection (CDI); increasing evidence supports FMT in severe or fulminant Clostridioides difficile infection (SFCDI). However, the multifactorial mechanisms that underpin the efficacy of FMT are not fully understood. Systems biology approaches using high-throughput technologies may help with mechanistic dissection of host-microbial interactions. Here, we have undertaken a deep phenomics study on four adults receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…FMT is an effective option for the resolution of rCDI and is being used around the world increasingly. Moreover, recent studies show its efficacy in treating the first episode of CDI as well as its repeated use can treat severe and fulminant CDI forms[ 60 ]. Although the concept of the method is simple, it is a labor-intensive procedure and requires the acceptance of the patient to be treated with this kind of transplant, even if FMT-derived capsules are used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FMT is an effective option for the resolution of rCDI and is being used around the world increasingly. Moreover, recent studies show its efficacy in treating the first episode of CDI as well as its repeated use can treat severe and fulminant CDI forms[ 60 ]. Although the concept of the method is simple, it is a labor-intensive procedure and requires the acceptance of the patient to be treated with this kind of transplant, even if FMT-derived capsules are used.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Monaghan et al [ 60 ] performed a systems biology-based study to interrogate the interaction among microbiome-metabolome-immune system in the context of FMT applied to patients with severe or fulminant CDI. They studied four patients unresponsive to antibiotic therapy and treated with sequential FMT.…”
Section: Immunological Effects Associated With Fmt Efficacy To Treat ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal studies and case series have reported the ability of faecal microbiota transplantation (FMT) to attenuate sepsis severity, in part through the restoration of butyrate-producing bacteria, gut barrier strengthening, innate immunity enhancement, immune repertoire alteration and pathogen clearance; however, some studies have reported lethal bacteraemia [ 153 ]. Notably, the immune repertoire is a variety of receptors on T cells and B cells that has a large sequence diversity to recognize different organismal molecules as a part of the adaptive immune system [ 154 ] and innate immunity, for example, macrophages, is an important host response against pathogenic gut organisms [ 74 ]. Meanwhile, butyrate is an important short-chain fatty acid that is categorized as an enterocyte energy source and a factor of anti-inflammation and anti-malignancy [ 155 ].…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…The emergence of FMT application in various ill states is owing to its significant efficacy in treating recurrent Clostridioides difficile infection (rCDI) ( Monaghan et al., 2021 ; Azimirad et al., 2022 ). The engraftment of microbial composition from a healthy donor to an appropriate patient thoroughly modifies the patient’s gut microbiota shifting it toward the donor’s microbial profile ( Wang et al., 2019 ).…”
Section: Microbiome-based Therapeutic Approaches In Gastric Cancermentioning
confidence: 99%